Response of 'Cratylia argentea' (Desvaux) O. Kuntzeto inoculation with 'Rhizobium' sp. and 'Bradyrhizobium' sp. strains - Mattar, Eduardo P. L.; Barros, Tiago T. V.; Brasileiro, Bruno P.; Mattielo, Edson M.; Coelho, Marcia R. R.; Gama, Guilherme F. V.; Dias, Denise C. F. dos S. (Australian Journal of Crop Science, 2018)
'Cratylia argentea' is a neotropical leguminous shrub that exhibits symbiosis with nitrogen (N) fixing bacteria and high levels of protein. Thus, it has potential for animal feed and green manure. In spite of its potential, few cultivars are registered for the species and there is little information in regard to its interaction with N-fixing microorganisms. The aim of this study was to evaluate the effect of inoculation with rhizobium strains on the growth and concentration of N in 'Cratylia argentea'. Seeds were inoculated with two strains of 'Rhizobium' sp.,CR 33 (BR10243) and CR42 (BR10244), and four strains of 'Bradyrhizobium' sp., CR52 (BR10257), CPAC-B10, SEMIA 6464 (BR3262), and SEMIA 6462 (BR3267), and sown in pots filled with sand and vermiculite in a greenhouse. After 150 days we evaluated the number of nodules, shoot and nodules dry matter, total nitrogen and crude protein contents for the shoots. The plants inoculated with CR 52 exhibited nodulation, with nodular efficiency of 0.189 and relative efficiency of 66.14%; it is possible to observe the effect of nodulation as of 85 days after sowing. Based on the obtained results it was identified the strain that showed symbiosis with 'C. argentea' and presents potential to be used as a commercial inoculant.